Wind Turbine Blade Dynamics Simulation under the Effect of Atmospheric Turbulence - Amr Ismaiel (Ital Publication, 2023)
Wind energy is one of the fastest growing sources of renewable energy because of its cleanliness and sustainability. Due to the turbulent nature of wind, a wind turbine experiences severe dynamic loading and faces the danger of fatigue failure. In addition, severe blade deflections imply failure by tower strikes. For this reason, the study of blade deflections under different turbulence conditions is of high importance. In this work, a wind turbine’s blade is simulated under different turbulent conditions. Four different wind fields are generated with a mean wind velocity of 12 m/s and turbulence intensities of 1, 10, 25, and 50%. The blade deflections are calculated in the out-of-plane and in-plane directions as a time-marching series with different blade azimuth positions. The higher the turbulence intensity, the severer the fluctuations of the deflections around its mean value. For the 50% turbulence intensity, the standard deviation of the out-of-plane deflection is 600% larger than that of the 1% turbulence intensity case. The maximum deflections increase significantly as well. A maximum of 3.78 m of out-of-plane tip deflection leads to the danger of a tower strike. And a positive tip deflection of 0.07 m in the in-plane direction indicates that the blade goes against its natural behavior and against the inertial loads while rotating. Continuous monitoring of wind conditions is a must, to put the turbine on brake in cases of gusts and severe turbulence. In areas of high turbulence, downwind turbines can provide a better alternative to allow blade deflections without the danger of tower strikes. Doi: 10.28991/ESJ-2023-07-01-012 Full Text: PDF